Cholesterol: An important actor on the cancer immune scene - Halimi, Hossein; Farjadian, Shirin (Frontiers in Immunology, 2022)
Based on the structural and signaling roles of cholesterol, which are necessary for immune cell activity, high concentrations of cholesterol and its metabolites not only trigger malignant cell activities but also impede immune responses against cancer cells. To proliferate and evade immune responses, tumor cells overcome environmental restrictions by changing their metabolic and signaling pathways. Overexpression of mevalonate pathway enzymes and low-density lipoprotein receptor cause elevated cholesterol synthesis and uptake, respectively. Accordingly, cholesterol can be considered as both a cause and an effect of cancer. Variations in the effects of blood cholesterol levels on the outcome of different types of cancer may depend on the stage of cancer. However, positive effects of cholesterol-lowering drugs have been reported in the treatment of patients with some malignancies.